(untitled) (Advances in Military Technology, 2022)
Asymmetric and underground warfare are of very tight relation. The absolute superiority of the coalition forces on the ground and air makes the underground space an additional tricky battlefield. The risk to be buried in the improvised tunnels or shafts is high but acceptable for the enemy, whose survivability on the surface is low. When enemy decides to make use of the underground space for his benefit, the coalition forces have to predict the location of underground openings. There are existing and recently excavated drifts. The first ones could be created by nature or dug by people. The enemy can utilize them as dugouts, assembly or logistic points. The recently excavated drifts could be utilized by the same way or offensively. Cave outlets could be used as firing points. No coalition facility can be safe against undermining. The article would like to explain the geotechnical conditions that can facilitate or hamper the enemy’s effort to make use of the underground space.